A geochemical and petrographical investigation of the low-grade tin deposits in the Bobbejaankop granite at the Zaaiplaats Tin Mine - Von Gruenewaldt, G. (Gerhard), 1942- (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 1984.